The conditions of demand and supply in the market of organic agriculture in Poland compared to selected European countries - Piotr Kulyk; Mariola Michalowska; Paulina Paluszkiewicz (Institute of Economic Research (IER), 2017)
Research background: Organic farming is a practical response to the ecological consequences of non-organic management of natural resources. Interest in the organic food market is growing both among producers and consumers. What has influenced this is, on the one hand, the demand for organic products, and on the other, the support for organic farming from the national budget and the budget of the European Union. Purpose of the article: In the article we have shown an attempt to identify the key factors influencing the development of the organic food market as well as the state of organic farming in Poland compared to individual European Union countries. Particular attention has been paid to the mechanisms of support for organic farming that enables farmers to keep a farming system based on ecological production methods not disturbing natural environmantal balance and allowing to undertake activities that are particularly beneficial for environmental protection ensuring the continuance and development of present and future generations. Seeking justification for the promotion of organic agricultural producers a reference has been made to the market failure, with particular emphasis on the problems of socio-economic development. Methodology/methods: The conditions for the development of the organic food market are shown in the context of the analysis of the literature on the problems of organic farming, the available empirical research, as well as the results of own survey conducted among respondents in Lubuskie Voivodeship and data from the Central Statistical Office, Eurostat and IJHARS. Findings: Polish organic food market is growing rapidly. However its significance in Poland is not great in the total agricultural production. The level and structure of consumption of organic food market is determined by the income of consumers, as well as their increasing environmental awareness. An important element influencing the development of organic farming is a system of support for organic farming.
Keywords: Q56; 330; organic farming; demand factors; supply factors